2018
DOI: 10.32674/jis.v8i1.167
|View full text |Cite
|
Sign up to set email alerts
|

“It Just Messes Your Mind”: U.S. International Students’ Perspectives of and Experiences with Academic Text Sourcing

Abstract: This critical case study explored how six international students enrolled in two U.S. universities perceived and understood the concept of plagiarism. Through our participants’ stories, we challenged a system that insists on international students’ conformity, without adequate knowledge or training, to a U.S. or Western system of text borrowing and sourcing that may be different from what the students have learned in their home countries. Our study calls for educational rather than punitive means of addressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 22 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…This explanation is frequently noted in studies of plagiarism among international students, particularly those from non-Western countries. International students may have significantly different understandings of plagiarism as a result of differing cultural norms between their countries of origin and their host countries (Abasi, Akbari, & Graves, 2006;Hu & Lei, 2012;Isbell et al, 2018;Madray, 2013;Pennycook, 1996). Support for this explanation is found in research where incidences of academic dishonesty diminished after students were given specific instructions about what constitutes plagiarism (Dee & Jacob, 2012;Owens & White, 2013).…”
Section: Constructing the Intentional/ Unintentional Typologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation is frequently noted in studies of plagiarism among international students, particularly those from non-Western countries. International students may have significantly different understandings of plagiarism as a result of differing cultural norms between their countries of origin and their host countries (Abasi, Akbari, & Graves, 2006;Hu & Lei, 2012;Isbell et al, 2018;Madray, 2013;Pennycook, 1996). Support for this explanation is found in research where incidences of academic dishonesty diminished after students were given specific instructions about what constitutes plagiarism (Dee & Jacob, 2012;Owens & White, 2013).…”
Section: Constructing the Intentional/ Unintentional Typologiesmentioning
confidence: 99%
“…They clearly understood that academic institutions valued a particular type or style of communication but lacked the cultural and linguistic capital to meet those expectations (Bourdieu & Passeron, 1990;Collier & Morgan, 2008;Turner, 2011). For students such as Eve and Lupe (both of whom are immigrants) and perhaps even Monica (who communicated in a combination of English and Spanish), research on nonnative English speakers might point more simply to struggles with language acquisition skills to explain plagiarism (Amiri & Razmjoo, 2016;Isbell et al, 2018;Perkins et al, 2018). However, a key difference in the explanations offered by the students in this study is that their concerns about language skills are less about speaking English per se and more about speaking the language of academia.…”
Section: Research Question 1: Explanations For Plagiarismmentioning
confidence: 99%
“…International students have reported feeling a range of emotions including fear, confusion, shock and disbelief, guilt, and shame as they learned about academic integrity expectations or when accused of academic misconduct (Baird and Dooey 2014 ; Brooks et al 2011 ; Crook 2018 ; Dalal 2015 ; Isbell et al 2018 ). Support for students as they navigate disciplinary processes is also described as inadequate (Baird and Dooey 2014 ), suggesting significant gaps in policies and procedures for handling cases of academic misconduct.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, research that purposefully explores the emotions of international students around academic integrity and misconduct is limited. Knowing that the stress associated with accusations of misconduct can be significant (Baird and Dooey 2014 ; Brooks et al 2011 ; Crook 2018 ; Dalal 2015 ; Isbell et al 2018 ), we were interested in how international students felt upon encountering information about academic integrity and misconduct at Canadian postsecondary institutions. Our concern was that elevated levels of negative emotion might be related to reduced knowledge of academic integrity and misconduct.…”
Section: The Present Studymentioning
confidence: 99%
“…After learning about plagiarism by participating in interview questions asked by the research team, students still struggled to understand the significance of the concept because of cultural differences. The overall results indicated that a more basic explanation of plagiarism in an introductory course was needed (Isbell et al, 2018). Even for graduate students, Thompson et al (2017) concluded that institutions of higher education must provide adequate orientation programs to all incoming graduate, domestic, and international students, especially if there is confusion about paraphrasing practices.…”
Section: Introductionmentioning
confidence: 99%